Genre en plot georiënteerde narratief-kritiese eksegese van Evangeliemateriaal: Inleiding tot narratiewe kritiek - Aarde, Andries van (HTS teologiese studies, 2006)
Genre and plot oriented exegesis of Gospel material: Introducing narrative criticismThis contribution to methodology and hermeneutics, consisting of two articles, aim to argue for combining historical criticism and narrative criticism. The first article shows how genre orientation can provide hermeneutical cues for determining an appropriate exegetical model and method. The article aims to apply Gérard Genette’s narratology as a narrative-critical model for the exegesis of Gospel material. The article focuses on the role plot analysis fulfills in narrative criticism. This discussion is illustrated with examples from the Gospels of Mark, Luke, Matthew and John. The article concludes with a preface to the second article in which aspects such as point of view and focalization, time and space, and characterization will be discussed, also applied to Gospel material.